CircZFR functions in cancer from molecular networks to precision therapy - Nan, Jinniang; Li, Min; Li, Xinru; Guo, Yuqing; Cai, Ziye; Deng, Zekang; Zhan, Chengyi; Li, Jiacheng; Liu, Shuying; Chen, Ziyi; Huang, Zhenjun; Yang, Yihan (Frontiers in Genetics, 2025)
CircRNAs are a class of covalently closed circular non-coding RNAs formed through back-splicing of precursor mRNAs, lacking 5′ caps and 3′ poly(A) tails, and are widely present in eukaryotic cells. Advances in high-throughput sequencing have revealed that circRNAs regulate gene expression and participate in disease pathogenesis, often exhibiting dual oncogenic or tumor-suppressive roles in cancer. CircZFR primarily comprises two subtypes—hsa_circ_0072088 and hsa_circ_0000345—which are derived from exons of the ZFR gene located on chromosome 5q13.3. CircZFR plays a critical regulatory role in the progression of multiple malignancies. This review systematically summarizes recent research progress on circZFR across different cancer types, elucidating its molecular mechanisms in influencing tumor proliferation, invasion, metastasis, and drug resistance through acting as a miRNA sponge, modulating signaling pathways, or directly binding to proteins. Furthermore, this review integrates the interaction networks between circZFR and key regulatory factors, unveiling its multifaceted functions in remodeling the tumor microenvironment. This review emphasizes the aberrant expression patterns of circZFR and their clinical prognostic relevance in multiple cancers, including colorectal, pancreatic, thyroid, bladder, hepatocellular, breast, lung, and cervical carcinomas, discusses its potential as a novel diagnostic biomarker or therapeutic target, and aims to provide a theoretical basis for precision cancer therapy while highlighting its translational research prospects.